PENGELOLAAN PEMBELAJARAN PENDIDIKAN ANAK USIA DINI DI KB CERDAS KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR - Ahmad Denico (UIR PRESS, 2018)
The research was conducted at KB Smart Rokan Hilir Hamper Stone with data sources consisting of managers, educators, and students in Smart KB. The purpose of this study was to explain the management of early childhood education (PAUD) learning in Smart KB in Batu Hampar District, Rokan Hilir Regency. Data collection techniques in this study were interviews, observation, and documentation. The results of this study are (1) PAUD learning syllabus in the form of semester planning, weekly planning, and daily/meeting planning. Planning is done by paying attention to the level of development, needs, interests, and characteristics of students, and aspects of development include religious and moral, motoric, cognitive, language and social-emotional values. (2) The implementation of learning in Smart KB starts with (a) happy morning, (b) habituation activities, (c) transition, (d) environmental footing, (e) footing before playing, (f) footing during playing, (g) footing after playing, (h) introduction of prayer, and (i) closing. The implementation of learning uses the method of playing while learning through center class learning with the Beyond Center and Circle Time (BCCT) approach, and the question and answer method, stories, role-playing or direct field practice. Activities are carried out in a comfortable, safe, clean and healthy playing environment. (3) Assessment of learning in Smart KB is done by observing at any time not during the KBM until the learning is finished. through observation, recording anecdotes, and portfolios.